Systemic infection induced by intranasal inoculation of Bovine herpesvirus 1.1 in pregnant and non-pregnant rabbits - Valera, Alejandro Rafael (2013)
Bovine herpesvirus (BoHV) type 1.1 (BoHV-1.1) causes repeated outbreaks of upper respiratory disease and abortion in cattle. The systemic effects of BoHV-1.1 in rabbits, using intranasal inoculation are reported. Female rabbits were divided into four groups and inoculated with the virus 10 days before mating, and at 15 or 22 days of pregnancy. Studies of the clinical signs, antibody production, virus isolation, and DNA detection as well as histological and immunohistochemical studies were carried out on lungs, kidneys, spleen, placentas, uteri and foetal tissues. All virus-inoculated animals developed respiratory clinical signs and a humoral response. BoHV-1.1 was isolated from nasal swabs and plasma rich in leukocytes, and viral DNA was detected in blood, dead foetuses and placentas. Histopathological lesions were found in the respiratory tract and some placentas and foetuses were immunohistochemically positive. Intranasal inoculation might be useful to study the systemic effects of BoHV-1.1 infection in the rabbit model.